Two-Port Noise Suppression in Dual-Polarization Interferometric Fiber-Optic Gyroscope - Pei Li; Yulin Li; Fangyuan Chen; Chao Peng; Zhengbin Li (IEEE Photonics Journal, 2019)
Since the polarization non-reciprocity errors are canceled out through optical compensation in dual-polarization interferometric fiber-optic gyroscopes (IFOGs), two ports, namely, the reciprocal and nonreciprocal ports, are both feasible sensing output. In this work, we propose and demonstrate a weighted subtraction method for noise suppression that utilizes the partial correlated two-port signals simultaneously. The relative intensity noise has reduced to 56.2% of its original value in the experiment and agrees with the theoretical analysis; as a result, the angle random walk is suppressed from ${\text{5.7}}\;\times\;{ \text{10}}^{-{\text{2}}}$ to ${\text{3.2}}\;\times\;{ \text{10}}^{-{{2\circ}}}/\sqrt{\mathrm{h}}$ with a 2-km-long fiber. The improvement on short- and long-term stability performance has been experimentally verified, which makes dual-polarization IFOG configuration promising for many applications.